Codex Theresianus of 1766: Codification Works, Structure, main Content and Significance of Roman Law Reception during its Conclusion Process - Roman Savuliak (Journal on European History of Law, 2023)
The purpose of the article is a step-by-step review of the codification works on the Codex Theresianus conclusion of 1766 and the outlining of the structure and the analysis of the main content of all Draft Code revisions, as well as clarifying the significance of the reception of Roman law during its conclusion. Hence, the author outlined the general work schedule of the Compilation Commission in Brno, which contained the primary structure of the Draft of Codex Theresianus. So, the content of the revisions of the Draft Code text, developed by the Compilation Commission, the Legislative Commission headed by Josef Azzoni, and the Legislative Commission under the supervision of Hofrat Zenker, were considered. In the process of this research, the author identified certain differences in the structure and revealed the peculiarities of some provisions in different versions. The durability of the Roman tradition of civil-law institutions and the content of some of their norms and, accordingly, the connection of the civil-law doctrine of the Austrian Empire with Roman law have been ascertained. In addition, the article broadly presents an analysis of the state of research in Ukrainian historical and legal science, both modern and at the end of the 19th – beginning of the 20th centuries, history of the sources of law, including the Draft of Codex Theresianus, and individual institutions of civil law of the Habsburg monarchy.